Editorial: Evolving Cosmographies - Sophie Chiari (Journal of Early Modern Studies)
This editorial is intended to frame the special issue of the Journal of Early Modern Studies devoted to The Circulation of Cosmographical Knowledge in Early Modern Europe. Providing early modern definitions of cosmography and differentiating between cosmography and geography, it takes stock of the latest scholarly publications on the subject and sheds light on the various contributions in this issue. In the presentation of the various sections, it emphasizes fresh perspectives and methodologies likely to open up new interpretive paths in the field of cosmography.